Effect of Alpha-2 Agonists on the Locomotor Activity in Adult Zebrafish - Saranya, R; Ramasamy, T; Ramesh, S; Srinivasan. M.R (The Indian Veterinary Journal, 2024)
This study aimed to validate zebrafish as a suitable model for investigating the sedative impact of alpha-2 adrenergic receptor agonists. Zebrafish were exposed to xylazine (500 and 1000 µg/L), clonidine (50 and 500 µg/L), and dexmedetomidine (5 and 50 µg/L), and their locomotor activity was recorded using a Sony 13.6MP digital camera at 5-minute intervals up to 45 min post-exposure. Kinovea software was used to track and analyze the distance travelled and the swimming speed. Xylazine exhibited decreased locomotor activity at 500 µg/L but increased activity at 1000 µg/L, possibly indicating overlapping effects on α-1 receptor adrenergic receptors. Clonidine showed no significant reduction, possibly because of its lower affinity to the zebrafish α-2 receptor compared to the humanα-2 receptor, or could have lower absorption through the skin and gills due to the low logP value of clonidine. Dexmedetomidine significantly decreased the locomotor activity due to its 10 times higher α-2 adrenergic receptor selectivity as compared to xylazine and clonidine. These findings support the use of adult zebrafish as an alternative model to explore the effects of α-2 receptor agonists in drug discovery research.